Documenting the Ephemeral: reconsidering the idea of presence in discussions on performance - Ayerbe (Universidad de Deusto – Bilbao/Vizcaya, Spain), Nerea (Revista Brasileira de Estudos da Presença, 2022)
The category of presence plays a major role in the most accepted definitions of performance art. This centrality of the ephemeral presence of the artist’s body has prevented an appreciation of performance documentation in all its importance. Taking Peggy Phelan’s position as representative of the prevailing paradigm, this article presents its main objections and intends to broaden the concept of presence in its application to performance to accommodate the documentation processes.